Kemiskinan Ekstrem, Ketimpangan Dan Pertumbuhan Ekonomi Di Indonesia - Putri Indah Lestari; Bernadette Robiani; Sukanto Sukanto (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This study aims to analyze the conditions and distribution patterns of Extreme Poverty, Inequality and Economic Growth in Indonesia, and the relationship between Indonesia's economic growth and Extreme Poverty itself. The data used is quantitative secondary data from TNP2K for extreme poverty data, and GRDP for each province, namely 34 provinces in Indonesia in the 2021-2022 period. The analysis technique used is Klassen Typology Analysis and Partial Correlation Analysis. Based on the research results show that extreme poverty has a strong relationship with economic inequality. As well as the relationship between Extreme Poverty, Inequality and Economic Growth as a control variable does not really have a big impact on changes in Indonesia's economic development.